Association between Vitamin K Epoxide Reductase (VKORC1) -1639G>A Polymorphism and Osteoporosis in Postmenopausal Women - Kutluturk, Faruk; Inanir, Ahmet; Rustemoglu, Aydin; Kaya, Suheyla U.; Demir, Ayse K.; Dursun, Gul; Yigit, Serbulent (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2018)
Introductıon: Osteoporosis is a common disease, and several factors contribute to its development. Recently, there has been increasing evidence that vitamin K (VK) plays a critical role in maintaining bone strength. Vitamin K serves as a co-factor for the γ-carboxylation of particular proteins to convert specific glutamic acid residues to γ-carboxyglutamic acid residues. This process involves two enzymes, γ-glutamyl carboxylase and vitamin K epoxide reductase (VKORC1). The number of studies investigating the effects of VKORC1 gene mutations on bone mineral density in postmenopausal osteoporosis patients is limited. The aim of this study was to investigate the relationship between the VKORC1 -1639G>A polymorphism and osteoporosis in postmenopausal Turkish women. Methods: The study group consisted of 176 postmenopausal women with osteoporosis and 140 healthy postmenopausal women. The selection criteria for the healthy controls included non-osteoporotic bone mineral density (BMD) and similar demographic characteristics to the osteoporosis group. The genotyping of the VKORC1 -1639G>A polymorphism was conducted using the restriction fragment-length polymorphism method. Results: We found that the genotype frequencies of the GG, GA and AA genotypes were 25.6, 64.2 and 10.2% in the patients and 33.6, 55.8 and 10.7% in the controls, respectively. In the patient and control groups, the genotype distribution of the studied locus was found to be non-compatible with Hardy–Weinberg equilibrium. We found a nonsignificant association between the -1639G>A polymorphism in the VKORC1 gene and osteoporosis in postmenopausal Turkish women. Conclusion: We have shown that the VKORC1 -1639G>A polymorphism is not a risk factor for postmenopausal osteoporosis.
Keywords: osteoporosis